Morphological Regionalization Strengthening the Conzenian Method - Arat, Muzaffer Ali. (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book is about how to make the method of morphological regionalization, proposed in the early 1960s, more useful and practicable for planning, urban design and architecture. This book is about cities; more precisely, about how cities can be characterized based on the main elements of urban form. It provides a systematic way of description and explanation of the historico-geographical structure of the urban landscape. It offers a step-by-step methodology for the identification of morphological regions as a key tool for planning practice and townscape management. The book is divided in seven parts. The first part is the introduction, motivation, research goal and objectives, and the structure of the book. The second part of the book offers an overview of urban morphology, urban morphological approaches, the concept of morphological region and its past applications worldwide. The third part is the methodological procedures for the implementation of this morphological approach to cities. The fourth and fifth parts are the implementation of this methodology into two case studies, Istanbul and Antequera. The sixth part offers a discussion of results. And, finally, the seventh part is constituted by a set of conclusions.
Introduction -- Urban morphology and the historico-geographical approach -- Refining the method of morphological regionalization -- Istanbul -- Antequera -- On the application of the method -- Conclusions.
Keywords: Design; Architecture; Sustainable architecture; Design; Architecture; Sustainable Architecture/Green Buildings